Värdet av tystnad - Asséhn, Josefin (2017)
Since the spring 2003 the tenant-owner home association the Terrace in Upplands Väsby municipality lies straight under the approach route to Arlanda Airport’s new third landing chute. Noise levels of over 70 dB have been measured in the area, which exceeds National Board of Housing’s, values for traffic noise at a terrace in connection to housing. By using the method of hedonisk pricing the essay tries to find out if there exists a willingness to pay to reduce the noise in the area. The development of the square metre price's in the Terrace is compared with a reference area, Bollstanäs, which is in many respects equal to the Terrace. The striking difference is however that Bollstanäs is not disturbed by the noise from the airplanes. The Terrace and Bollstanäs also diverges in other aspects, and in order to conduct a correct comparison these divergences are identified through a surrounding world analysis, and is adjusted for with the aid of the value transfer method Benefit Transfer. Those discrepancies that are found are the buildings' age, the monthly rent, the distance to the Shopping Mall and the distance to the commuter train station. The result shows that both before and after the adjustments have been made for the deviating characteristics the Terrace has consistently higher price level than Bollstanäs. This can be interpreted as if does not exist a willingness to pay for noise reduction among the hardest exposed in Upplands Väsby. In the result analysis, possible reasons are discussed to the lack of willingness to pay. In addition to the self-evident conclusion that noise is not experienced as a problem worth to pay for, reasons as incorrect adjustment values, omitted adjustment factors, asymmetric information and distorted primary data are treated.